Public-Private Partnerships in the Context of Public Investment Management in Ukraine : An Assessment - World Bank (World Bank, Washington, DC, 2016)
Ukraines vast needs in infrastructure coupled with a constrained fiscal space require concerted efforts in strengthening public investment management. Investments in infrastructure are important for fostering economic growth. Translating public investments into assets crucially depends on how efficiently all types of public investments are management. The structure to handle PPPs is currently inadequate to access the global PPP market. Since a PPP system needs to be built on the foundations of a workable PIM system, the prospects for Ukraine attracting international standard investments from the global PPP market may appear to be out of reach for the time being. Recent reforming legislation aimed at fixing some of the issues highlighted in the 2012 PIM Assessment is encouraging but much will depend on the effectiveness of the implementation and the capacity of the institutional actors to understand and absorb them. This Assessment must by its very nature capture the situation at the time of the Assessment rather than an expectation of future potential.